Demographic structure of a threatened palm (Euterpe edulis Mart.) in a fragmented landscape of Atlantic Forest in northeastern Brazil - Melina Oliveira Melito (Acta Botânica Brasílica, 2014)
At the northern limits of the range of the palm species Euterpe edulis there is an endemic ecotype, known as the "Bahia" ecotype, which is distinguished by its reddish crownshaft and low seed production. Unfortunately, little is known about its demographic characteristics. Therefore, we contrasted the density of E. edulis populations in the Una region, in the southern part of the Bahia state, Brazil, with that of other populations of the species in southern and southeastern Brazil. In addition, within the Una region, we compared a long-protected forest fragment (F1) with three recently protected fragments (F2, F3, and F4), in terms of demographic parameters and plant size, in order to determine what influence, if any, time since protection has on E. edulis populations. Population densities within the Una region were higher than in regions where E. edulis populations are stressed by harvesting or intense seed predation but much lower than in regions with well protected populations. Among the Una fragments, density was highest in F1 and lowest in F2. The proportion of individuals at the various developmental stages differed among the fragments (χ²=25.219, df=12, p=0.014). Diameter at ground level, height, and number of leaves correlated positively among themselves and negatively with population density. For all developmental stages, F1 surpassed the other fragments in terms of densities and plant sizes. It is likely that the newly protected populations suffer the lingering effects of previous harvesting, which are reflected in their demography and in the size of their individual members. The viability of this low-density endemic ecotype must be established in order to assess the conservation status of the species on a regional scale.